Pretest probability of coronary artery disease as a factor for optimizing invasive diagnostics in routine clinical practice - M. A. Simonyan; T. Yu. Kalyuta; E. N. Genkal; O. M. Posnenkova; V. I. Gridnev (Российский кардиологический журнал)
According to the European Society of Cardiology guidelines, patients with chest pain requires the calculation of pretest probability (PTP) of coronary artery disease (CAD), followed by the identification of diagnostic tactics.Aim. To analyze the registry of patients with stable CAD in order to assess the frequency of PTP calculation, as well as the validity of diagnostic tactics choice depending on its level.Material and methods. The data of the registry of patients with stable CAD for the periods from 2012 to 2014 and from 2017 to 2019 were analyzed. We assessed the number of CAD patients, proportion of men, and distribution of patients depending on angina functional class. In addition, data on PTP calculation, as well as distribution of patients and diagnostic strategy selected depending on its value was analyzed. To assess differences (p) in pairwise comparisons, Student’s t-test was used. Differences were considered significant at p<0,05. Statistical analysis was performed using Microsoft Office Excel 2010 (Microsoft, USA) and STATISTICA 6.0 (StatSoft Inc., USA).Results. In 2017-2019, the number of detected CAD cases and proportion of men increased. In both time periods, an insufficient level of calculating PTP of CAD remains. In patients with intermediate PTP, 15-85% of priority tactics are invasive interventions, and with high PTP, the percentage of invasive methods does not reach the proper level, which does not correspond to modern guidelines for the management of CAD patients and leads to misappropriation of funds and healthcare resources.Conclusion. According to medical records, PTP can be determined in less than half of patients. In CAD patients with intermediate PTP, non-invasive studies are not carried out in full, since coronary angiography is preferred. In patients with a high PTP, invasive diagnostics is insufficient.